-2(5r+4)=-(r-10)

Simple and best practice solution for -2(5r+4)=-(r-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(5r+4)=-(r-10) equation:



-2(5r+4)=-(r-10)
We move all terms to the left:
-2(5r+4)-(-(r-10))=0
We multiply parentheses
-10r-(-(r-10))-8=0
We calculate terms in parentheses: -(-(r-10)), so:
-(r-10)
We get rid of parentheses
-r+10
We add all the numbers together, and all the variables
-1r+10
Back to the equation:
-(-1r+10)
We get rid of parentheses
-10r+1r-10-8=0
We add all the numbers together, and all the variables
-9r-18=0
We move all terms containing r to the left, all other terms to the right
-9r=18
r=18/-9
r=-2

You can always share this solution

See similar equations:

| 7n+3=3n+227 | | 8(3w+7)/5=1 | | 2(x?9)?2???32=0 | | (2x^2-1)^2=16 | | 3y-(y+4)=4y-8 | | 1000=1.8(10^2x) | | 85+5x=100 | | 7n-13=71 | | 9n-4=5 | | -22-6x=-4x+10 | | 3-9y=5y | | 3x–7=x+3 | | 6. 3x–7=x+3 | | 9-3y=5y | | 9x÷8+6=3x÷6+2 | | -11-x=x+5 | | u/8=6u= | | 6x-16,3=53-x | | u/11=6u= | | 11w=8470w= | | 6a+12=2a+14 | | –5p=25 | | 10w-10=7w | | 4^x+8=9*2^x | | 4x+8=9*2x | | (38)+(6x-6)(÷2)=7x-4 | | (38)+(6x-6)=7x-4 | | 10x+4x+4+9=8x+3+5x | | 50-3x=70-6x | | 4y+y/5=2.1 | | b-2(b-20)=9b | | | | |

Equations solver categories